The content analysis, the presentation and the instrument readability of Indonesian proficiency test - Rahmawati Laili Etika, Suwandi Sarwiji, Saddhono Kundharu, Setiawan Budhi, (Universiti Pendidikan Sultan Idris, 2017)
The content analysis, the presentation and the instrument readability of Indonesian proficiency test by Rahmawati Laili Etika, Suwandi Sarwiji, Saddhono Kundharu, Setiawan Budhi,